Removal of Mercury (II) from Aqueous Solutions Using the Leaves of the Rambai Tree (Baccaurea motleyana) - Sen, Tushar; Azman, A.; Maitra, S.; Dutta, B. (Water Environment Federation, 2011)
This study was undertaken to evaluate the biosorption potential of a natural, low-cost biosorbent, Rambai leaves (Baccaurea motleyana), to remove trace amounts of Hg(II) from aqueous solutions. It was found that the amount of Hg(II) biosorption by Rambai leaves increased with initial metal ion concentration, contact time, and solution pH but decreased as the amount of biosorbent increased. The maximum biosorption capacity was 121.95 mg/g for an initial concentration range of 5 to 120 ppb. Overall, kinetic studies showed that the Hg(II) biosorption process followed pseudo-second-order kinetics based on pseudo-first-order and intraparticle diffusion models. Isotherm data revealed that the biosorption process followed both Freundlich and Langmuir isotherms. The value of separation factor, RL, from the Langmuir equation and rate of biosorption, n, from the Freundlich model also indicated favourable adsorption.